Insulin resistance and lipid alterations in subclinical hypothyroidism - Sridevi, Atluri (Medknow Publications & Media Pvt Ltd, 2012)
INTRODUCTION: It is known that dyslipidemia and increased insulin resistance were associated with overt hypothyroidism, but their association with subclinical hypothyroidism is conflicting. Aim was to evaluate insulin resistance and lipid alterations in subclinical hypothyroidism. METHODS: Fifty consecutive cases of subclinical hypothyroidism are the subjects of the study. The cases are compared with age, gender and BMI matched controls. Lipid profile, insulin levels, FPG are assessed after overnight fast. Insulin resistance is calculated using HOMA-IR. The correlation between TSH& lipid prolife, TSH & IR was assessed. RESULTS: Total cholesterol (169.37±32.83 vs. 154.5±18.71, p= 0.031) & low density lipoprotein cholesterol (105.76±26.92vs 93.80±16.67, p=0.037) were significantly higher in cases compared to controls. High density lipoprotein cholesterol (44.23±4.65 vs 42.26±3.20, p=0.0507) was lower in cases which showed a trend towards significance. Triglycerides (97.64±39.44 vs. 92.96±43.49,p=0.65) , fasting insulin levels (11.74±7.16 vs 9.77±5.54,p=0.211) and Insulin resistance (2.30±1.49 vs. 1.78±1.09, p=0.11) were elevated but did not differ significantly between the two groups. CONCLUSION: Subclinical hypothyroidism is associated with elevation of TC, LDL-C and non significant increase in TG and insulin resistance. Both lipid profile and insulin resistance did not correlate with severity of hypothyroidism.